Pemulihan Ekonomi Nasional di Masa Pandemi Covid-19 Melalui Trans-formasi Strategi Bisnis UMKM - Hildawati (Future Science, 2021)
Prior to the Covid-19 pandemic, UMKM contributed to Indonesia's GDP up to 60%. This fact shows that it has been proven to be able to reduce poverty and be able to absorb more workers than other business entities, thereby reducing unemployment. The main problem of this research is how is the transformation of UMKM business strategy in the recovery of the national economy during the Covid-19 pandemic? The purpose of this study is to describe that by transforming business strategies, UMKM have the potential for national economic recovery during the Covid-19 pandemic. This research is a qualitative descriptive study. The data collection technique used is literature study. Sources of data in this study using textbooks, articles, journals and statistical data. Data analysis technique is descriptive analysis. The results of the study show that in dealing with the Covid-19 pandemic, one of the important steps that the government can take for the recovery of the national economy is to pay attention to the growth and development of UMKM in Indonesia. Along with the current digitalization era, to realize innovative, productive and adaptive UMKM in the midst of the Covid-19 pandemic, UMKM need to transform digital-based business strategies. The contributions of this research include theoretical contributions and methodological contributions. The implication of this research is that the transformation of business strategy is a simple concept that can be carried out in the recovery of the national economy during the Covid-19 pandemic.